Influence of isomorphous substitution of metal ion on the low-frequency dielectric dispersion in NH2(CH3)2Al1−xCrx(SO4)2⋅6H2O ferroelectrics. (1st February 2017) - Kapustianyk, V.; Eliyashevskyy, Yu.; Czapla, Z.; Dacko, S.; Rudyk, V.; Sereda, S.; Ostapenko, N.
ABSTRACT: This paper is devoted to the study of the influence of metal ion isomorphous substitution on the ferroelastic-ferroelectric phase transition and dispersion caused by the motion of domain walls in dimethylammonium metal sulfate hexahydrate DMAAl1 − x Cr x S ferroelectric crystals ( x = 0, 0.065, 0.2). It is shown that such a substitution significantly changes the phase transition temperature and parameters of the dielectric dispersion. These changes are explained in terms of interaction between the metal-hydrate complexes and DMA groups that carry the dipole moment and due to this they are responsible for the phase transitions and motion of the domain walls.